Purification and characterization of heparin degrading enzyme by isolated bacteria from brackish sediment - Khanitchadecha, Prapasri; Pulsawat, Waranyoo (Asia-Pacific Journal of Science and Technology, 2016)
The heparinase-producing bacteria was isolated from brackish sediment and identified by morphological characteristic and 16S rRNA gene. The nucleotide sequence of 16S rRNA indicated highest similarity (97%-100%) with genus Aeromonas. The isolate was subsequently described as Aeromonas sp. RYA_En1. The crude intracellular enzyme produced by Aeromonas sp. RYA_En1 was partial purified by ammonium sulphate, ion exchange and gel filtration column chromatography, respectively. The active fraction obtained from gel filtration chromatography yielded enzyme production and enzyme specific activity of 410 U/L and 0.63 U/mg protein, respectively. Then, the purified fraction was determined for the optimal temperature and pH for the enzyme activities which were at 37°C and pH of 7.0, respectively. In addition, the molecular weight of the purified enzyme determined by the SDS-PAGE was approximately 90 kDa.